Josephson effects at iron pnictide superconductors: Approaching phase‐sensitive experiments. Issue 1 (9th November 2016) - Schmidt, Stefan; Döring, Sebastian; Hasan, Noor; Schmidl, Frank; Tympel, Volker; Kurth, Fritz; Iida, Kazumasa; Ikuta, Hiroshi; Wolf, Thomas; Seidel, Paul
Abstract : The electrical transport in the pnictides especially the quasiparticle tunnelling and Josephson effects in inhomogeneous superconducting systems can provide information on the symmetry of the order parameter. Different kinds of Josephson junctions with one or two pnictide electrodes were realised and their properties were experimentally studied in detail (e.g., current–voltage characteristics, microwave response, current‐phase relations, dependencies on temperature and external magnetic field). These results were compared to well‐known Josephson junctions and recent theories taking into account the special properties (multiband superconductivity, exotic pairing symmetry) of the pnictides. By combination of two junctions in different crystal directions with different barrier transparencies one forms corner junctions or SQUIDs as phase‐sensitive devices. If the technological problems can be solved the investigations on such devices will finally clear up the symmetry of the pnictides, directly. These investigations will lead to a better understanding of fundamental properties of the pnictides as well as to a realistic judgement on the potential for applications of pnictides in superconducting electronics and sensor applications, both established ones and novel ones utilising the special pnictide properties. Abstract : The authors present fundamental investigations of three different Josephson junction geometries based on pnictide thin films and single crystals. Different transparencies and high I c RN products of up to 1 mV at 4.2 K could be obtained. These findings may enable direct measurement of the pairing symmetry by connecting two different junction types. A detailed analysis of the implementation design is given.